Hepatitis C Virus-Infected Apoptotic Hepatocytes Program Macrophages and Hepatic Stellate Cells for Liver Inflammation and Fibrosis Development: Role of Ethanol as a Second Hit - Murali Ganesan; Larisa Y. Poluektova; Chijioke Enweluzo; Kusum K. Kharbanda; Natalia A. Osna (Biomolecules, 2018)
Hepatocyte apoptosis is a crucially important mechanism for liver disease pathogenesis, and the engulfment of apoptotic bodies (AB) by non-parenchymal cells serves as a leading mechanism of inflammation and fibrosis progression. Previously, we have shown that hepatitis C virus (HCV) and alcohol metabolites induce massive apoptosis in hepatocytes and the spread of HCV-infection to the neighboring uninfected cells. Here, we hypothesize that the capturing of AB by non-parenchymal cells, macrophages and hepatic stellate cells (HSC) changes their phenotype to promote inflammation and fibrosis. In this regard, we generated AB from Huh7.5CYP2E1 (RLW) cells also treated with an acetaldehyde-generating system (AGS) and incubated them with human monocyte-derived macrophages (MDMs) and HSC (LX2 cells). Activation of inflammasomes and pro-fibrotic markers has been tested by RT-PCR and linked to HCV expression and AGS-induced lipid peroxidation in RLW cells. After exposure to AB we observed activation of inflammasomes in MDMs, with a higher effect of AB HCV+, further enhanced by incubation of MDMs with ethanol. In HSC, activation of inflammasomes was modest; however, HCV and AGS exposure induced pro-fibrotic changes. We conclude that HCV as well as lipid peroxidation-adducted proteins packaged in AB may serve as a vehicle for delivery of parenchymal cell cargo to non-parenchymal cells to activate inflammasomes and pro-fibrotic genes and promote liver inflammation and fibrosis.